HEPTAPLEURUM CONNATUM (ARALIACEAE): A NEW SPECIES OF HEPTAPLEURUM FROM SARAWAK, MALAYSIAN BORNEO - RAMNOR, NORAZIRA; AHMAD PUAD, AIDA SHAFREENA; FRODIN†, DAVID G. (Research Center for Biology, 2024)
A new Heptapleurum species from Sarawak, Borneo is described and illustrated as Heptapleurum connatum N.Ramnor, A.Puad & D.G.Frodin. It is an epiphyte or treelet recorded at various vegetation types such as near riverbank, limestone forests, remnant forests, hills and peat swamp forests from 10‒1,219 m asl. It is distinguished from H. truncatifructum by being slightly larger in size, having more second-order venations with narrow spacing between them, more flowers per umbel, and more stigmata on fused style. A distribution map of the species in Sarawak has also been constructed.